Anticoagulant Activity of Dayak Onion Bulb (Eleutherine bulbosa) Extract on Human Blood Samples - Anik Handayati; Syamsul Arifin; Monica Putji Astuti (Health Notions, 2021)
Cardiovascular disease can occur due to disruption of the hemostatic system by forming blood clots in blood vessels, or commonly known as deep vein thrombosis. The curative action that has been carried out in the form of heparin anticoagulant administration had many side effects such as bleeding, hematuria, thrombocytopenia, and hypersensitivity; therefore, alternative anticoagulant ingredients such as onion bulbs have emerged. Dayak onion bulb (Eleutherine bulbosa) is known to contain eleutherinol compound, which has anticoagulant activity. This study aims to determine the potential anticoagulant activity of Dayak onion bulbs extract (Eleutherine bulbosa) on human blood samples. This anticoagulant activity test was carried out by observing the length of time for blood clotting in the extract treatment group with several concentrations (0, 10, 12.5, 16, 25, and 50%) by Clotting Time (Lee-White) method. The results showed a significant delay in blood coagulation time in the group treated with Dayak onion bulbs extract as increasing the concentration. About 50% Dayak onion onion bulb extract was showed a twofold increase in blood coagulation time thanthat of no extract administration. So that, Dayak bulb onion has the opportunity to be an alternative natural anticoagulant. Keywords: anticoagulants; Dayak onion bulbs (Eleutherine bulbosa); clotting time